The literature book - Canton, James (New York, New York DK Publishing, 2016)
Examines "the greatest works of world literature, from the Iliad to Don Quixote to The Great Gatsby. Around 100 ... articles explore landmark novels, short stories, plays, and poetry that reinvented the art of writing in their time, whether Ancient Greece, post-classical Europe, or modern-day Korea"--Amazon.com
Includes bibliographical references and index
1
Keywords: Literature -- History and criticism; Literature; Criticism, interpretation, etc